Light Enhanced Calcification in Hermatypic Corals: New Insights from Light Spectral Responses - Cohen, Itay; Dubinsky, Zvy; Erez, Jonathan (Frontiers in Marine Science, 2016)
Light enhanced calcification (LEC) is a well documented phenomenon in reef-building corals. The main mechanism proposed for LEC is that photosynthetic CO2 uptake by the algal symbionts elevates the pH and thus enhances calcification. We evaluated the role of light and of photosynthesis on calcification by assessing the response of the corals Porites lutea and Acropora variabilis to different components of the light spectrum. Calcification and photosynthesis of both species decreased under “lagoon” blue, green and red light (peaks at 500, 550 and 600nm respectively). However, blue light (peak at 455nm) enhanced calcification rates of P. lutea and A. variabilis (up to 4.1 and 10.5 fold of dark values, respectively) reaching levels comparable to those measured under full spectrum illumination. However, contrary to our expectations, photosynthetic oxygen production was considerably reduced under blue light, to the extent that it remained below the compensation point even under illumination as high as 400µmol photons m-2 s-1. It is the first time that a direct effect of light not mediated by the photosynthetic process has been demonstrated to trigger LEC in corals. We propose that blue light signaling, and animal receptors thereof may be involved in the enhancement of calcification by hermatypic corals.